Primary repair of long gap esophageal atresia in a neonate employing circular myotomy on upper pouch and a novel hemicircular myotomy on the distal pouch - Faryal.G. Afridi; Nicholas. Shorter; Richard. Vaughan; Susan. Neptune; Shailinder. Singh (Elsevier, 2019)
Introduction: Pure esophageal atresia (EA) with long gap between the pouches remains a challenge for primary repair. Several techniques to facilitate primary repair in long gap EA have been described: complete mobilization of proximal and/or distal esophageal pouch, single or double circular myotomies or spiral myotomy of upper pouch, circular myotomy of both upper and lower pouch, flaps raised from the upper pouch to bridge the gap and external traction sutures. Some of these techniques are not routinely performed for anatomical reasons or unfamiliarity with the technique. Complete mobilization of upper pouch with circular myotomy is standard and often favored approach. Complete mobilization of lower pouch with or without circular myotomy is described. It has a risk of impairing the blood supply to the lower pouch due to segmental nature of its blood supply. We present a novel case of primary repair of this defect using a circular myotomy on upper pouch along with a hemicircular myotomy of the lower pouch without complete circumferential mobilization of the lower esophageal pouch. This allowed adequate lengthening of the lower pouch without compromising its blood supply facilitating a minimal tension primary repair. Case: We report the case of a 38 4/7 term infant with intra-uterine growth retardation (IUGR) and Tetralogy of Fallot (TOF) with a long 4.5 cm gap pure esophageal atresia who was repaired aged 16 weeks. Per-operative gap assessment revealed the gap to more than 4 vertebral bodies. Even after complete mobilization of the upper esophageal pouch, a 2.5 cm (cm) gap persisted. The upper pouch was narrow and hence unsuitable to facilitate flap reconstruction. A single circular myotomy was performed on the upper esophageal pouch approximately 1 cm proximal to its blind end. The lower pouch was then mobilized, taking care that its blood supply was not compromised. This still left a one cm gap that was overcome by performing a hemicircular (180°) myotomy on the lower esophageal pouch approximately 1 cm away from the blind end. A tension free primary esophageal anastomosis was then performed. Post operatively patient developed a stricture which was dilated successfully to 12 Fr (4 mm). No other complications are reported. Conclusion: Hemicircular myotomy of the distal esophageal pouch can be employed successfully to achieve primary repair in cases of long gap esophageal atresia. This technique does not require full circumferential mobilization of lower pouch as required with full circular myotomy and has less risk of compromising blood supply to the distal esophageal pouch decreasing risks of anastomotic leak, failure and esophageal motility of lower pouch.